Design of control laws to guarantee mutual exclusion constraints in a network of linear Min-Plus systems with disturbance inputs - Bouazza, S.; Amari, S.; Hassine, H. (Information sciences, 2025)
This paper is dedicated to solve the control problem for aclass of timed Petri nets with disturbance inputs and which is subject toMutual Exclusion Constraints (MECs). More precisely, it is aboutguaranteeing a set of MEC in a network of timed event graphs with some uncontrollable source transitions. Based on the Min-Plus formalisms, analytical approachesto the design of control laws to meet these marking specifications areproposed. For this, sufficient conditions to compute causal statefeedbacks are identified accordingto the initial marking of the considered Petri net. To illustrateproven control techniques, an application of a disassembly systemapplication is discussed. The calculated controllers are translated into timed and marked places, related to the initial model of a network of timed events graphs. It is represented by 2 intermediate transitions and 5 monitor places. These places act as supervisors preventing the violation of MECs.